Photinian Opponents in Hilary of Poitiers's Commentarium in Matthaeum - Beckwith, Carl L. (The journal of ecclesiastical history, 2007)
Since the end of the nineteenth century scholars have been divided on the identity of Hilary of Poitiers's opponents in his Commentarium in Matthaeum. As he wrote the treatise in the early 350s, it is assumed that his opponents, if real and not contrived, must be ‘Arian’. What has not been sufficiently considered is whether Hilary may be addressing other fourth-century theological positions. In this article it will be argued that two key passages from the commentary, generally used to indicate an awareness of ‘Arian’ ideas, actually suggest an engagement with the theological views commonly associated with Photinus of Sirmium.